Emperors and usurpers : an historical commentary on Cassius Dio's Roman history books 79(78)-80(80) (A.D. 217-229) - Scott, Andrew G. (American classical studies ;, 2018)
This historical commentary examines books 79(78)-80(80) of Cassius Dio's Roman History, which cover the period from the death of Caracalla in 217 B.C. to the reign of Severus Alexander and Cassius Dio's retirement from political life in A.D. 229 Cassius Dio, a Roman senator, provides a valuable eyewitness account of this turbulent period, which was marked by the assassination of Caracalla; the rise of Macrinus, Rome's first equestrian emperor, and his subsequent overthrow; the tempestuous, and by all accounts peculiar, reign of Elagabalus; and the continuation of the Severan dynasty under the young Severus Alexander. In addition to elucidating important passages from these books, this study assesses Cassius Dio's political life and its relationship to his literary career; his call to history and time of composition; his historical method; and his attitude toward and subsequent presentation of the later Severan dynasty. In its investigation of books 79(78)-80(79), the work assesses an important stretch of Dio's actual text, which for other parts has been preserved largely in epitome and excerpts. Finally, the work aims to fill a gap in scholarship, as no commentary on these books of Cassius Dio's history has been produced since the nineteenth century, and its publication coincides with a renewed interest in the history and historiography of the Severan period.